2010
DOI: 10.1377/hlthaff.2010.0238
|View full text |Cite
|
Sign up to set email alerts
|

analysis & commentary Measuring Patient Experience As A Strategy For Improving Primary Care

Abstract: Patients value the interpersonal aspects of their health care experiences. However, faced with multiple resource demands, primary care practices may question the value of collecting and acting upon survey data that measure patients' experiences of care. The Consumer Assessment of Healthcare Providers and Systems (CAHPS) suite of surveys and quality improvement tools supports the systematic collection of data on patient experience. Collecting and reporting CAHPS data can improve patients' experiences, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
247
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(257 citation statements)
references
References 27 publications
4
247
0
6
Order By: Relevance
“…They found that racial/ethnic groups were more likely to regard cultural competency and the provision of a holistic approach to care as important to healthcare quality. Patient experience of care reflects the value of the interpersonal aspects of their health care experience and complements health-related quality of life evaluations in assessing care from the patient's perspective (18). Information derived from direct evaluation of patient experience of care can be used to identify areas for improvement and support changes in care provision with the aim of improving the overall quality of care for patients.…”
Section: Discussionmentioning
confidence: 99%
“…They found that racial/ethnic groups were more likely to regard cultural competency and the provision of a holistic approach to care as important to healthcare quality. Patient experience of care reflects the value of the interpersonal aspects of their health care experience and complements health-related quality of life evaluations in assessing care from the patient's perspective (18). Information derived from direct evaluation of patient experience of care can be used to identify areas for improvement and support changes in care provision with the aim of improving the overall quality of care for patients.…”
Section: Discussionmentioning
confidence: 99%
“…10,13,14 Patient-experience data can be important to system transformation when physicians and practice administrators use and act on the data. 9,12,15,16 CAHPS surveys were designed to use information from the patient's perspective on care to improve its quality and make it more patient focused. 17 The CAHPS surveys are now the US standard for information about patient experience of care because of their reliability, content, and validity.…”
Section: Introductionmentioning
confidence: 99%
“…This finding reinforces previous analyses of the effectiveness of patient surveys in QI, namely, that their usefulness depends on design, standardization, construct validity, reliability, and internal/external validity. 12,15 Hence, the initial corporate decision to administer the CG-CAHPS survey as a part of the data-monitoring system for PCMH and QI activities enabled the practice leaders at all levels at these FQHC sites to effectively act on their patient-experience data and make changes.…”
mentioning
confidence: 99%
“…Interviews revealed that leaders believed that their organizations placed a strong emphasis on improving the collection and quality of key performance measures, primarily the HEDIS quality of care indicators and patient experience measures. 30 HEDIS data were described as central to directing the organization's foci for future improvement e orts.…”
Section: Implementation Facilitatorsmentioning
confidence: 99%